Radiation-induced formation of polyacrylic acid-protein covalent conjugates - Mustafaev, M; Bayülken, S; Ergen, E; Erkol, AY; Ardagil, N (PERGAMON-ELSEVIER SCIENCE LTD, 2001)
Radiation-induced formation of water-soluble covalent conjugates of polyacrylic acid (PAA) with negatively charged proteins - bovine serum albumin (BSA) and superoxide dismutase (SOD)- was investigated at neutral pH. Aqueous solutions of PAA, BSA, SOD and their mixtures (PAA-BSA, PAA-Cu2+-BSA, PAA-SOD) have been irradiated with Co-60 gamma -rays and the resulting changes have been measured by high-performance liquid chromatography and UV-Visible spectrophotometry. Crosslinking and formation of water-soluble conjugates of PAA with BSA molecules upon irradiation were observed in the PAA-BSA and PAA-Cu2+ -BSA mixtures. In contrast to these systems, Cu(II), Zn(II) ions in the structure of SOD molecules protect the free protein, and the protein component of PAA-SOD mixtures against radiation damage, and prevent the PAA-SOD covalent conjugate formation. The mechanism of observed protection effect is discussed. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: BOVINE SUPEROXIDE DISMUTASE; SERUM-ALBUMIN; COMPLEXES; WATER; CU2+; Chemistry; Nuclear Science & Technology; Physics